Age & Achievement - Grissom, James B. (Education Policy Analysis Archives, 2004)
There is continuing controversy about the optimal or appropriate age at which children should start school. The purpose of this study is to examine the relationship between age and achievement. It is an attempt to evaluate the hypothesis that older students fare better academically than their younger classmates. Findings indicate that on average for students in elementary school there is positive linear relationship between age and achievement for age normal peers. Even though there is positive linear relationship, the difference in average test scores between the oldest and youngest students is not great and by the time students reach 10th grade the positive linear relationship has disappeared. For overage students there is on average a negative linear relationship between age and achievement at all grade levels. That is, the negative relationship between age and achievement remains constant over time. These results argue against modifying entrance age policies, delaying school entry, implementing transitional kindergarten or first grade programs or retaining students to improve educational achievement. Policies and practices that make students older than their classmates inversely affect their educational achievement.